“The invasions are not over”: Pragmatic approach to Sámi aesthetics and criticism through the discussion of young adult literature - Stueng, Saia Marilena (Sámi dieđalaš áigečála, 2024)
This research reports on an empirical study of the reception of Sámi literature from the perspective of Sámi theories of aesthetics: Dåajmijes vuekie (Kappfjell& Gaski 2018), the pragmatic notion of Sámi aesthetics, and the theory that Sámi authors serve as pathfinders for readers, guiding them to new visions of a Sámi future (Kuokkanen 2004). The research is based on the contents of Girjemiella podcasts (2020) that presented reviews of five Sámi literary works. These podcasts emphasized the qualities of usefulness, readability, and relatability. The aesthetic functions proposed by Jan Mukařovský (1977b (1943)) serve as the foundation for this analysis of the reviews and critiques. According to the critics, literary works that are relatable and engaging comport best with these functions, and thus also serve as pathfinders to the reception of literature as one way to utilize the arts. In this article I suggest that the quality of Sámi arts is deeply rooted in a practical and pragmatic attitude toward self-determination.
Keywords: Sámi aesthetics; literature; reception; epistemology; literature reviews; aesthetic functions; self-determination